Efficacy and Safety of Biosimilar Cetuximab Versus Innovator Cetuximab in Indian Patients With Head and Neck Cancer: A Multicenter, Randomized, Double-Blind, Phase III Trial - Kumar Prabhash; Chetan Deshmukh; Hemant Malhotra; Atul Sharma; Minish Jain; Nilesh Dhamne; Rajnish Nagarakar; Prasantha Ganesan; Vijay K. Mahobia; Chandan K. Das; Rejnish Kumar; Prakash S. Shivanna; et al. (JCO Global Oncology)
PURPOSESquamous cell carcinoma of the head and neck (SCCHN) is the sixth most common cancer, with approximately 225,419 new cases with over 125,000 deaths annually in India. This trial compared the efficacy and safety of biosimilar cetuximab versus innovator cetuximab (IC) in combination with platinum-based chemotherapy in patients with recurrent locoregional or metastatic SCCHN.METHODSThis phase III trial is a multicenter, randomized, double-blind and parallel group study performed in Indian patients with recurrent locoregional or metastatic SCCHN. Patients were randomly assigned in 2:1 ratio to receive biosimilar cetuximab and IC in combination with cisplatin and fluorouracil via intravenous infusions. The primary end points were disease control rate (DCR) and overall response rate (ORR) as per response evaluation criteria in solid tumors version 1.1. The secondary end points included pharmacokinetics (PK), immunogenicity, safety, and tolerability.RESULTSOf 180 patients enrolled, 120 patients received biosimilar cetuximab and 60 patients received IC treatment. No significant statistical difference was observed in the primary outcomes between two groups. Treatment difference in DCR and ORR response was found to be –5.21 (90% CI, –8.94 to –1.48) and –4.79 (90% CI, –19.42 to 9.84), respectively, indicating noninferiority to reference product. The incidence of treatment-emergent adverse events (AEs; biosimilar cetuximab: 89.2% v IC: 91.7%; P = .8364) and serious AEs (biosimilar cetuximab: 23.3% v IC: 13.3%; P = .0603) and PK parameters were comparable between treatment groups. The immunogenicity findings showed higher incidence of anticetuximab antibodies in the biosimilar cetuximab group compared with the IC group at the end of Study.CONCLUSIONThe findings of this study demonstrated noninferiority along with comparable PK, safety, and immunogenicity of biosimilar cetuximab and IC in patients with recurrent or metastatic SCCHN.